Adoptation of engine for smaller enterprise (E4SE) performance measurement system (PMS) in small project based company in Malaysia - Lim, Pei Jiun (2016)
This research was conducted to test the validity of the new performance measurement system which is the Engine For Smaller Enterprise, E4SE model and make the recommendation implementation of the E4SE model in the small project based companies in the SMEs industry. The performance measurement system of E4SE model is the tool to evaluate the internal and the external of the enterprises through different aspect such as through management level and level competitors or rivals. Thus, the future strategic plan will be developed in order to sustain survival of the companies. This performance measurement system framework includes the three main elements, Strategy Formulation Activities (SFA), Strategy Administration Activities (SAA) and Performance. The survey questionnaire was distributed to the management cadre or the company’s owner-manager of the company respectively. A total sample of 49 samples was used in this study. Research objective had been achieved through the data analysis finalized by using Microsoft Excel 2007. The results of this study showed that the small project based companies in the SMEs industry is suitable to implement the modified E4SE model based on the data collected and analysis in Malaysia. From this study, the implementations of the E4SE model in the small and medium industry not only increase the potential of the company, but also raising the awareness of the implementation performance measurement system in the organization.